Microbial community variation in pristine and polluted nearshore Antarctic sediments - Shane Powell; John Bowman; Snape, I; Stark, JS (2003)
Two molecular methods were used to investigate the microbial population of Antarctic marine sediments to determine the effects of petroleum and heavy metal pollution. Sediment samples were collected in a nested design from impacted and non-impacted locations. A detailed description of the diversity of the microbial population in two samples was obtained using 16S ribosomal DNA clone libraries constructed from an impacted and a non-impacted location. The clone libraries were very similar with the exception of two sequence clusters containing clones from only the impacted location. All samples were analysed by denaturing gradient gel electrophoresis. The band patterns generated were transformed into a presence/absence matrix and a multivariate approach was used to test for differences in the locations. Statistically significant differences were observed both between and within locations. Impacted locations showed a greater variability within themselves than the control locations. Correlations between the community patterns and environmental variables suggested that pollution was one of a number of factors affecting the microbial community composition. Â© 2003 Federation of European Microbiological Societies. Published by Elsevier Science B.V. All rights reserved.